Lipid Profile among Ischemic and Haemorrhagic Stroke Patients - Dey, SK; Ahmed, S; Rahman, KM; Uddin, MJ; Alam, MR; Bhattacharjee, M; Mondal, G; Israil, A (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):176-80. The abstract of this article is available on the PubMed website